A unique and rare presentation of Henoch-Schonlein purpura: a case report - V. K., Rahees; Jimo, Likta N.; Golmei, Namganglung; Sananganba, Raj Kumar; Chettri, Priyanka (International Journal of Contemporary Pediatrics, 2024)
Henoch-Schönlein purpura (HSP), or IgA vasculitis, is a common small vessel vasculitis in children, typically presenting with palpable purpura, abdominal pain, arthritis, and renal involvement. However, atypical presentations can delay diagnosis and management. A 12-year-old girl presented with multiple episodes of loose stools and abdominal pain. The initial diagnosis focused on acute gastroenteritis, and she was treated symptomatically. Subsequently, she developed urticarial rashes with breathing difficulty, complicating the diagnosis. Despite symptomatic treatment, she experienced severe abdominal pain, hematemesis and melena. Further investigations revealed antral gastritis, duodenitis, and cystitis. On the 14th day of admission, the patient developed characteristic palpable purpura on the lower limbs. Skin biopsy confirmed leukocytoclastic vasculitis with IgA deposits, consistent with HSP. The patient recovered with supportive care and remained symptom-free on follow-up. This case underscores the importance of considering HSP in pediatric patients with atypical presentations, such as gastrointestinal symptoms and urticaria without initial purpura. Early recognition and appropriate management are essential to prevent complications and ensure favourable outcomes. The variability in HSP presentations necessitates a high index of suspicion for timely diagnosis and treatment.